Nanocrystalline ZrN particles embedded in Zr-Fe-Cu-Al-Ni amorphous matrix - Bab, Marisa Alejandra (2002)
Melt-spun Zr64Al7Cu17Ni10Fe2 amorphous ribbons were milled under nitrogen atmosphere for different times. The resulting nitrided powders were studied by x-ray diffraction, Mössbauer spectroscopy and differential scanning calorimetry. The formation of nanosized crystalline particles, with cubic δ-ZrN structure, dispersed in the amorphous matrix was observed along with a change in the composition of the amorphous phase. Prolonged milling leads to the additional precipitation of late transition metals (Fe,Ni,Cu). The nitride particles affect the crystallization behavior and modify the thermal stability of the amorphous alloy.